Virality and Public Moral Judgment: A Study of Netizen Comments on The Gus Elham Video Case - Sofi Juliyanti; Dias Senja Juniko (Journal of World Science, 2026)
The case of a viral video featuring young preacher Gus Elham showing himself kissing a small child during da'wah activities has sparked widespread controversy on social media, especially Instagram. Various counter-netizens' comments expressed sharp criticism of the act, which was deemed inappropriate and exceeded the ethical limits of interaction between adults and children. This study analyzes the pattern of netizens' criticism in video uploads of Gus Elham's case recordings to understand how digital society builds moral narratives against religious figures in digital public spaces. This study uses a descriptive qualitative approach through the analysis of Instagram comment content, focusing on netizens' counter-comments as the main data. The results of the study show the dominance of ethical criticism, demands for child protection, moral delegitimization of religious figures, and calls for social and legal responsibility. These findings show the role of netizens as active social actors in shaping public ethics discourse and social control over religious figures in the digital space. This study recommends strengthening digital da'wah ethics literacy and preparing guidelines for public interaction ethics for religious figures on social media.